Comparison of the effects of ethanol extract with aqueous extract of purple sweet potato tuber in expression of SOD-2, SOD-3, and eNOS on human vascular endothelial cells exposed by H2O2 in-Vitro - I Made Jawi; I G K Arijana; I Wayan Putu Sutirta Yasa; AAN Subawa (Journal of Global Pharma Technology, 2017)
Aqueous extract of purple sweet potato tubers have antioxidant potential in animal and human vascular endothelial, through increased expression of superoxide dismutase. This study aims to prove the comparison between ethanol extract and aqueous extract of purple sweet potato tubers increasing the expression of superoxide dismutase -2, superoxide dismutase -3, and endothelial nitric oxide synthase in human vascular endothelium. This study was an experimental study of the vascular endothelial cells which underwent oxidative stress in vitro, which is protected by ethanol extract or aqueous extract of purple sweet potato tuber at various concentrations. Observation of the superoxide dismutase -2, superoxide dismutase -3, and endothelial nitric oxide synthase in endothelial cells is done using the method immunohistochemistry with monoclonal antibodies. The results showed an increase in superoxide dismutase - 2, superoxide dismutase -3, and endothelial nitric oxide synthase was significantly (p < 0.05) in endothelium protected by ethanol extract or water extract of purple sweet potato tubers. The ethanol extract only showed its effect at concentration of 1.5625 µg/ml for superoxide dismutase -2 and superoxide dismutase -3. The effect of aqueous extract were at a concentration of 1.5625–3.125µg/ml. From these results it can be concluded that the ethanol extract or aqueous extract of purple sweet potato tubers can protect endothelial cells from oxidative stress through increased expression of superoxide dismutase -2 and superoxide dismutase -3. The ethanol extract requires much lower concentrations to show its effect compared with aqueous extracts. Keywords: Aqueous extract or ethanol extract of purple sweet potato, Superoxide dismutase, Human umbilical vein endothelial cells.